Medial and Lateral Patellofemoral Joint Retinaculum Thickness in People With Patellofemoral Pain: A Case‐Control Study. (24th September 2018) - Lack, Simon; Anthony, Luke; Noake, James; Brennan, Kay; Zhang, Bairu; Morrissey, Dylan
Abstract : Objectives: To measure the medial and lateral retinaculum thickness in individuals with and without patellofemoral pain using ultrasound and to assess associations with the symptom duration and function. Methods: Medial and lateral patellofemoral joint retinaculum thicknesses of 32 knees (16 with patellofemoral pain and 16 asymptomatic) were measured with B‐mode ultrasound at 0.5, 1, and 1.5 cm from the patella border. Participants with patellofemoral pain completed a Kujala questionnaire, and both groups underwent a single‐leg squat performance assessment. Two‐way analyses of variance (site × group) determined the overall effect, and Cohen d values were calculated to describe the magnitude of the difference for each measurement. Results: The groups were matched for age, height, and weight. Compared to controls, participants with patellofemoral pain had thicker lateral (overall effect, P  = .03) and medial (overall effect, P  < 0.01) retinacula. No correlations between retinaculum thickness and Kujala scores (lateral retinaculum, r  = 0.106 [0.5 cm], –0.093 [1 cm], and –0.207 [1.5 cm]; and medial retinaculum, r  = 0.059, 0.109, and –0.219), symptom duration (lateral retinaculum, r  = 0.001, –0.041, and 0.302; and medial retinaculum, r  = –0.027, –0.358, and –0.346), or single‐leg squat performance scores (lateral retinaculum, r  = 0.051, 0.114, and 0.046; and medial retinaculum, r  = –0.119, –0.292, and 0.011) were observed. Conclusions: Increased lateral and medial retinaculum thickness in individuals with patellofemoral pain compared to controls identifies structural changes that may be associated with the pathogenesis of patellofemoral pain. The absence of a significant correlation between retinaculum thickness and the symptom duration or function further shows a lack of an association between structure and function in individuals with patellofemoral pain.